The natural resource management to support tourism: A traditional knowledge approach in Pegunungan Arfak Nature Reserve, West Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sonbait LY, Manik H, Warmetan H, Wambrauw YLD, Sagrim M, Djitmau DA, Wanggai J, Rettob BB, Murdjoko A. 2021. The natural resource management to support tourism: A traditional knowledge approach in Pegunungan Arfak Nature Reserve, West Papua, Indonesia. Biodiversitas 22: 4466-4474. Pegunungan Arfak Nature Reserve (PANR) is administratively located in three districts of West Papua, namely Manokwari, Manokwari Selatan, and Pegunungan Arfak that has diversity of protected flora and fauna. Therefore, it is crucial to study the local products for the development of ecotourism models based on local wisdom in supporting the potential economy of communities in the Pegunungan Arfak reserve. The data were obtained from direct interviews with communities around the nature reserve area through related government agencies in Manokwari District. The finding of this research highlighted that local people in Pegunungan Arfak (the Hatam-Moile sub-tribe) still use traditional knowledge for their livelihood. Most of the activities were the utilization of natural resources such as flora and fauna. They understand how to manage the natural resource to earn economic benefit along with the implementation of their traditional concept to promote the sustainability of nature. The biodiversity and social-cultural richness of local people in Pegunungan Arfak have value to be developed together with traditional ecological knowledge in sustainable nature management where local people earn benefits and nature is conserved simultaneously.
Keywords: ecotourism, endemic species, ethnobiology, New Guinea.